Digital Business Models in Sport - Tomanek, Mateusz; Cieslinski, Wojciech; Polasik, Michal (Routledge Research in Sport Business and Management, 2022)
Digital technologies are having a profound impact on sport business, opening up new opportunities to generate income and value. This book explores the phenomenon of digitization in sport management, with a particular focus on business models and how they are being transformed in this new digital era. The book explains how business models describe and underpin contemporary sport business, and how flexibility is the key to unlocking value in an era of rapid technological change. It presents case studies of the impact of digitization on sport organizations, in both amateur and professional contexts, including cutting-edge topics such as the business of football, sponsorship communication, athlete engagement, micropayments and wearable devices. The final chapter summarizes current knowledge on digital business models and looks ahead at possible future directions for sport business in the digital era. This is fascinating reading for any advanced student, researcher or practitioner working in sport management who wants to better understand the challenges and opportunities presented by digital technology for the sport industry.